Mucílago de cacao (Theobroma cacao L.) de origen trinitario (CCN-51) como medio antioxidante para la obtención de almíbar de manzana (Pyrus malus L.) - Mora Ibarra, Kerly Arianna (2019)
This research investigation was carried out in the Chemistry Laboratory, located in the Experimental Farm "La María" of the State Technical University of Quevedo, located at km 7 ½ of the Quevedo - El Empalme road, San Felipe Campus; Canton Mocache, Province of Los Ríos. The syrup is a method of preservation of fruits used to prolong the shelf life of the product, compared to microbiological development, which is generated through a process of immersion of the fruit in a sugary solution such as government water, with different concentrations of sucrose (common sugar), which determines the type of syrup that will be obtained, thus lowering the water activity (Aw) in a relationship inversely proportional to its formulation. The cocoa mucilage (pulp) of the Trinitarian variety (CCN-51), is one of the main by-products in the industrial sector that is not commonly used and / or commercialized, due to the ignorance of its properties, therefore, it is intended to give added value and thus obtain an innovative product, such as the production of apple syrup. Four levels of cocoa mucilage were evaluated in the production of apple syrup, demonstrating that the best treatment was T1 (Apple syrup with 5% of national cocoa mucilage), presenting the best organoleptic characteristics, and treatment T5 (Syrup of apple with 20% of trinitarian cocoa mucilage) giving similar characteristics to T1, demonstrating that the trinitarian variety mucilage in high concentrations significantly influences the national cocoa mucilage. Keywords: Syrup, mucilage, levels, preserve.